GAMBARAN PENGETAHUAN, SIKAP IBU, PELAYANAN, DAN PETUGAS KESEHATAN TERHADAP KEJADIAN MORNING SICKNESS - Rini Winangsih; Dewa Ayu Ari Kusumayuni; Gusti Ayu Putu Widya Wulandari (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2021)
Background: Morning sickness is one of the problems of first trimester pregnant women that must receive special attention. The cause of morning sickness in first trimester pregnant women is influenced by various factors, namely mother's knowledge, mother's attitude, health service facilities and health workers. This study aims to describe the knowledge, attitudes of mothers, services, and health workers on the incidence of morning sickness in first trimester pregnant women in Batuagung Village. Methods: This type of research is descriptive with a cross sectional design. The total population of 50 pregnant women in the first trimester who experienced morning sickness, the sample in this study amounted to 32 people, sampling by purposive sampling. The instrument in this study used a questionnaire distributed online via google form. Data analysis with descriptive method to obtain variable frequency distribution. Results From the results of the study, it was found that the mother’s knowledge about morning sickness was quite good 70%, knowledge about the impact of morning sickness is good 85%, mother’s attitude about morning sickness is good 85%, the quality of health care facilities is good 80%, attitude of health workers is good 80%. Conclusions: Knowledge, attitudes of mothers, services and health workers on the incidence of morning sickness in first trimester pregnant women in Batuagung Village are very good.